2011
DOI: 10.1227/neu.0b013e31820c04a9
|View full text |Cite
|
Sign up to set email alerts
|

Differential Efficacy of Electric Motor Cortex Stimulation and Lesioning of the Dorsal Root Entry Zone for Continuous vs Paroxysmal Pain After Brachial Plexus Avulsion

Abstract: EMCS was ineffective for paroxysmal pain but moderately effective for continuous pain. DREZotomy was highly effective for paroxysmal pain but moderately effective for continuous pain. It may be prudent to use EMCS for residual continuous pain after DREZotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 22 publications
0
31
0
4
Order By: Relevance
“…However, we observed that appropriate BMI training reduced pain even in these patients (Supplementary Table 3), suggesting that it could be an alternative to mirror therapy. Moreover, some patients in this study had also undergone lesioning of the dorsal root entry zone (DREZotomy)44 and reported residual pain after surgery. The BMI training significantly reduced the scores for continuous pain in the residual pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed that appropriate BMI training reduced pain even in these patients (Supplementary Table 3), suggesting that it could be an alternative to mirror therapy. Moreover, some patients in this study had also undergone lesioning of the dorsal root entry zone (DREZotomy)44 and reported residual pain after surgery. The BMI training significantly reduced the scores for continuous pain in the residual pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pain after BPRA is caused by several factors, as is the pain after amputation3. In particular, the paroxysmal pain after BPRA is hypothesized to originate from the affected spinal cord and is often relieved by DREZotomy44. Moreover, in BPRA patients, some motor and sensory functions of the arm partially remain.…”
Section: Methodsmentioning
confidence: 99%
“…1,13,58 Motor cortex stimulation (MCS) has also been undertaken with equivocal results influencing paroxysms more than continuous pain, 2,33 and spinal cord stimulation (SCS) has been reported with limited success. 15,64 No trials comparing neuromodulation treatments for BPA have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Paroxysmal pain in patients with brachial plexus avulsion responds to surgical intervention that involves lesion of the dorsal root entry zone, thereby selectively damaging second-order nociceptive neurons and sparing dorsal columns. [92][93][94] Paroxysmal extreme pain disorder is caused by a gain-of-function mutation in SCN9A, the gene encoding the sodium channel Na v 1.7, which is expressed by nociceptive fibres. 55 The paroxysmal pain that characterizes this rare condition is, therefore, presumed to be associated with abnormal activity in nociceptive fibres.…”
Section: Anatomical Denervationmentioning
confidence: 99%